Malay sketches - Swettenham, Frank Athelstane Sir 1850-1946 (Silverfish Malaysian classics)
Sir Frank Athelstane Swettenham was an important figure in Southeast Asia at the turn of the century. First posted to Singapore in 1871, his prompt mastery of colloquial Malay served him well throughout his career. In 1896, he became the first Resident General of the Federated Malay States, followed by his appointment as Governor and Commander in Chief of the Straits Settlements. Drawing on twenty-five years experience in Malaya, Swettenhem presents a series of sketches of the lush landscape of Malaya, and observations of the lives, customs, beliefs and superstitions of the locals.